INDONESIAN EFL POSTGRADUATE STUDENTS' PERCEPTION TOWARD ACCENT IN LISTENING COMPREHENSION - Maharani, Reynita Adlina (Premise: Journal of English Education and Applied Linguistics, 2023)
Listening comprehension has been one of the most challenging proficiency for EFL learners in Indonesia, including for postgraduate students. In this research, the researcher aims to investigate postgraduate students perception of accents within listening comprehension. Furthermore, this research employed a mixed method and an online open-ended questionnaire as the instrument. 33 Indonesian participants who attended Indonesian and Indian universities were willing to join the research. Moreover, the Questionnaire consisted of 11 questions that needed to be answered by the participants. In addition, the researcher analyzed the data by chart and percentage to show the difference between the participants responses. The result revealed that 93.9% of postgraduate students were primarily familiar with the American accent rather than the British accent throughout their education. It is because most of the schools in Indonesia adopt an American accent for their English course.Furthermore, 87.9% of the participants used an American accent when speaking in English, and 63.6% sometimes had difficulty understanding Americans. Additionally, 66.7% of the participants stated that the speaker's speed was the significant problem they had in listening comprehension. However, all of the participants found that accent also had the utmost role in listening comprehension because the accent they listened to correlated to their understanding of vocabulary being spoken by the speaker in the listening comprehension audio. Thus, based on the research, Indonesian postgraduate students perceived accent as pivotal in listening comprehension. The speaker's accent on the listening comprehension audio determined how well they could do the listening comprehension test.